Invitation of foreign colonists to Russia in the 1760s: The beginning of formation and implementation of colonization policy - G.V. Ibneyeva; A.I. Lebedeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the invitation of foreign colonists to Russia at the beginning of Catherine II’s reign. The purpose of the research is to reconstruct the initial stage of formation of colonization policy of the Russian Empire. The development of Catherine II’s legislation authorizing resettlement of foreigners to certain regions of the country has been analyzed on the basis of archival sources. Special attention has been paid to identification of the means and methods for implementation of the colonization policy, as well as to the mechanisms for attracting potential colonists. It has been demonstrated that institutionalization of special agents (commissioners, recruiters, and propagandists), whose field of activity was directly associated with potential colonists, became the main tool in implementation of the colonization policy. The paper concludes that a number of subjects (The Office of Foreign Guardianship, The Board of Foreign Affairs, Russian diplomats, commissioners, propagandists, minor emissary recruiters, callers, as well as the potential colonists themselves) interacted in the process of calling and sending colonists to Russia. The Russian government made attempts to fix the mechanism of inviting and sending colonists to new places of the settlement. In this case, it initially relied on its diplomatic agents abroad, who were not always able to successfully solve the tasks assigned to them. The mechanisms of attraction and resettlement of potential colonists to Russia were formed during the long period of time and changed depending on problems of the colonization policy throughout the second half of the 18th – the first quarter of the 19th centuries.